The Lattice of Subvarieties of Monadic Lukasiewicz Algebras - Abad, Manuel (2007)
In this paper we describe the lattice of subvarieties of the variety ofmonadic Łukasiewicz-Moisil algebras. We then characterize all these subvarieties by means of identities.